PERANCANGAN MESIN MODIFIKASI CAMSHAFT TIPE SINGLE CUTTER MENGGUNAKAN AUTODESK INVENTOR - Aljufri Aljufri; Abdul Rahman; Syarifah Akmal; Ranu Firmansyah; Abdul Ali Chaniago (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Camshaft is one of the main components of a 4-stroke motorcycle where the Camshaft has a function as a regulator of opening and closing valves in the working process of the engine itself.Â The profile of the camshaft that is thirsty due to friction so that it must be replaced with a new one or do cam turning using a grinder. The purpose of this design is to design a camshaft engine, which is designed to facilitate the work of mechanics, especially motorcycle mechanics. and can be used as a tool to modify the camshaft setandart into camshaft racing. This engine will be able to produce Camshaft racing. In the process of machine design is carried out in several stages, namely analyzing needs, defining and listing design requirements, designing product concepts, and designing products and documenting products in the form of machine design drawings. The energy source is supplied from electricity. The results of this design resulted in the design and working drawings of camshaft modified engine products including shafts, camshaft mounts, pulley mounts, engine frames, and transmission systems. In this design, camshafts will also be tested with 3 variations of camshaft profiles to determine the value of power and torque due to changes in camshaft diameter. From the three test results, standard camshaft variations and modifications found changes in power and torque values which increased in value by 1 hp and clutch slip occurred during the dayno process which showed a fracture at engine speed 8000 rpm.